Key Articles and Guidelines in the Primary Prevention of Ischemic Stroke. Issue 6 (11th February 2013) - Baker, William L.; Marrs, Joel C.; Davis, Lindsay E.; Nutescu, Edith A.; Shaun Rowe, A.; Ryan, Melody; Splinter, Michele Y.; Vardeny, Orly; Fagan, Susan C.
<x xml:space="preserve">Abstract</x> Ischemic stroke is a prevalent disease with a large burden on the health system. Preventive strategies, therefore, are paramount. Primary prevention is aimed at reducing the risk of stroke in asymptomatic people. The most effective prevention is through control of modifiable risk factors. Due to the large amount of literature available on this topic, this bibliography (the first of a 2‐part series) aims to provide a comprehensive resource for medical practitioners charged with caring for this population.